2016
DOI: 10.2135/cropsci2016.03.0182
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tropical Maize Germplasm with Tolerance to Drought, Nitrogen Deficiency, and Combined Heat and Drought Stresses

Abstract: The objective of this study was to evaluate Maize (Zea mays L.) elite lines currently available in CIMMYT's lowland tropical breeding program in Latin America under multiple abiotic stresses and identify lines with tolerance to drought, N deficiency, and combined heat and drought stress (HTDS). An incomplete line‐by‐tester design was used to evaluate 436 testcrosses under nonstressed conditions, 507 under N deficiency, 417 under drought stress (DS), and 368 under HTDS in 30 season‐by‐location combinations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
7
14
1
2
Order By: Relevance
“…The observed significant correlations between the same traits measured under DS, DSHTS as well as WW conditions suggest the presence of common genetic factors controlling expression of these traits under the three growing conditions. However, the observed weak correlations between grain yield under DS and DSHTS indicate the presence of independent genetic factors controlling yield performance under these conditions, which agrees with previous studies [4,34]. The significant association of grain yield under DS with yield under WW observed in our study is consistent with the findings of other researchers [4,36].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The observed significant correlations between the same traits measured under DS, DSHTS as well as WW conditions suggest the presence of common genetic factors controlling expression of these traits under the three growing conditions. However, the observed weak correlations between grain yield under DS and DSHTS indicate the presence of independent genetic factors controlling yield performance under these conditions, which agrees with previous studies [4,34]. The significant association of grain yield under DS with yield under WW observed in our study is consistent with the findings of other researchers [4,36].…”
Section: Discussionsupporting
confidence: 93%
“…The significant association of grain yield under DS with yield under WW observed in our study is consistent with the findings of other researchers [4,36]. This result, however, contradicts the findings of Trachsel et al [34] who reported very weak correlation (r = 0.075) between grain yield under optimum and that under stressed conditions. The strong correlation between grain yield and TB and BP demonstrated that these traits together with other secondary traits (ASI, EPP, ear and plant aspect cores, days to anthesis, and silking) should be included in an index to select promising genotypes under DSHTS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Yield at high N exhibited greater genetic variance (within heterotic groups and hybrids) and environmental variance, but lower residual variance than Yield −N . Greater genetic variance under high N when compared to low N has also been documented previously [43,44]. Conversely, genetic and environmental variance for harvest index at low N (HI −N ) were greater than at high N (HI +N ).…”
Section: Phenotypic Variation Of N-use Traitssupporting
confidence: 69%
“…The production of maize affects a large proportion of the world population. As a C4 plant, maize has a high photosynthetic efficiency and acquires considerable biomass under an appropriate nitrogen (N) supply [1]. Since the green revolution, farmers have tended to maximize N fertilization to increase crop yield [2].…”
Section: Introductionmentioning
confidence: 99%